2006
DOI: 10.1111/j.1574-6968.2006.00354.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of diarrhoeic faecal samples for enterotoxigenic, Shiga toxin-producing and typical or atypical enteropathogenicEscherichia coliin Kashmir, India

Abstract: Three hundred and twenty-six Escherichia coli isolates recovered from 326 human faecal specimens from sporadic cases of diarrhoea in Kashmir valley, India, were investigated for the presence of stx(1), stx(2), eaeA, hlyA and lt virulence genes. None of the samples was positive for stx genes or Shiga toxins by PCR or enzyme-linked immunosorbent assay. Twenty-three E. coli isolates showed the presence of the eaeA gene, whereas three isolates harboured the lt gene. Enteropathogenic E. coli (EPEC) belonged to 10 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
33
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 27 publications
(38 reference statements)
7
33
1
2
Order By: Relevance
“…Studies in both Brazil and Bangladesh have found clear seasonal peaks in tEPEC as well, but these peaks can occur at different times during the calendar year, possibly as a result of local meteorological patterns (3). From the present study, it appears that aEPEC is an emerging diarrheagenic pathogen, not only in industrialized countries, as previously described (1,6,22,29), but also in developing countries, like Mexico (7), Brazil (31), and India (32). aEPEC strains identified in Mexico were previously shown to possess lower levels of antibiotic resistance than other diarrhea-producing E. coli pathotypes in Mexico (7), suggesting that aEPEC strains may have recently been acquired in this country.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Studies in both Brazil and Bangladesh have found clear seasonal peaks in tEPEC as well, but these peaks can occur at different times during the calendar year, possibly as a result of local meteorological patterns (3). From the present study, it appears that aEPEC is an emerging diarrheagenic pathogen, not only in industrialized countries, as previously described (1,6,22,29), but also in developing countries, like Mexico (7), Brazil (31), and India (32). aEPEC strains identified in Mexico were previously shown to possess lower levels of antibiotic resistance than other diarrhea-producing E. coli pathotypes in Mexico (7), suggesting that aEPEC strains may have recently been acquired in this country.…”
Section: Discussionsupporting
confidence: 52%
“…tEPEC strains have been reported to most commonly infect infants Յ6 months old (21,23). It is possible that in Mexico, tEPEC prevalence is diminishing as aEPEC infection rates are increasing, a pattern already described for industrialized regions (29,31) and more recently for several developing countries (22,23,31,32). EIEC was the DEP with the highest degree of association with diarrhea, found in half of the subjects, revealing once more its virulence for infants in Mexico (24).…”
Section: Discussionmentioning
confidence: 96%
“…Although previous studies reported typical EPEC as the predominant strain in pediatric diarrhea in developing countries, recent data suggest that atypical EPEC are more prevalent than typical EPEC in both developing and developed countries (1,13,(22)(23)(24). Previous studies demonstrated significantly differing constituent ratios of typical EPEC to atypical EPEC in different regions in India, even when using the same classification method (8,25). The proportion of typical EPEC in our study is reasonable considering geographic variations in EPEC epidemiology.…”
Section: Discussionmentioning
confidence: 44%
“…The resistance rate of EPEC to ampicillin, cephalexin and ceftriaxone has risen to 74.5z-100z in Kashan, Iran. Infections caused by multi-drug resistant EPEC has also increased (8,9). Production of b-lactamase is the major mechanism underlying b-lactam antibiotic resistance in gram-negative bacilli (10).…”
Section: Discussionmentioning
confidence: 99%
“…These strains were recognized by the presence of the eae gene and the absence of the bfpA gene. Such detection pattern was important as atypical EPEC strains were considered emerging pathogens in several developing countries as well as Europe, in keeping with other studies such as; Toma et al, (2003), Vidal et al, (2005), Wani et al (2006), Alikhani et al (2006), Moreno et al (2008).…”
Section: Journal Of Biology and Life Sciencementioning
confidence: 52%